Exploring non-immersive virtual reality experiences in tourism: Empirical evidence from a world heritage site - Zhu, Chris; Wu, Don Chi Wai; Hall, Colin Michael; Fong, Lawrence Hoc Nang; Koupaei, Sara Naderi; Lin, Feifei (Wiley, 2023)
With the popularization of the concept of the metaverse, non-immersive virtual reality (VR) has become a focus of tourism destination marketing. Drawing upon telepresence theory, this study identifies the antecedents and consequences of telepresence to help interpret tourist behavior in the context of non-immersive VR experience. Results revealed that mental imagery and vividness positively predict tourist telepresence and satisfaction; Telepresence positively predicts satisfaction and intention during non-immersive VR experiences. Our work enriches telepresence theory by identifying the antecedents and consequences of telepresence in the context of non-immersive VR, and provides meaningful practical insights for similar attractions that adopt the technology.
Keywords: mental imagery; metaverse; non-immersive virtual reality; satisfaction; telepresence; travel intention; vividness